Manganese deficiency decreases pecan leaf photosynthesis by reducing the number of chloroplasts per unit leaf area - Henriques, Fernando (2009)
Effects of low Mn on pigment content, CO2 assimilation rate, leaf conductance and internal Co2 concentration of Carya illinoinensis Koch, cv. Kiowa